(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This study analyzes the ontogenetic formation of the immune system in children and the physiological, nutritional, and hygienic factors influencing its strengthening. The article examines age-dependent differentiation of innate and acquired immunity, morphofunctional maturation of lymphoid tissues, and development of immune responses based on scientific evidence. Research findings demonstrate the direct impact of rational nutrition, intestinal microbiota homeostasis, psychoemotional stability, and ecological conditions on immunogenic characteristics development. The article provides a theoretical foundation for developing preventive strategies in pediatric practice.